2019
DOI: 10.1021/acs.nanolett.9b03421
|View full text |Cite
|
Sign up to set email alerts
|

Position and Frequency Control of Strain-Induced Quantum Emitters in WSe2 Monolayers

Abstract: Future scalable and integrated quantum photonic systems require deterministic generation and control of multiple quantum emitters. Although various approaches for spatial and spectral control of the quantum emitters have been developed, on-chip control of both position and frequency is still a long-standing goal in solid-state quantum emitters. Here, we demonstrate simultaneous control of position and frequency of the quantum emitters from transition metal dichalcogenide monolayers. Atomically thin two-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…[ 3c,26 ] We envision that two or more emitters in hBN can be put in resonance by employing the strain methods using cantilever geometries, as an example. [ 3b,27 ] The technique is fully amenable to the engineering of emitter—cavity coupling, whereby the SPE ZPL can be strain tuned into resonance with the cavity mode. [ 4,28 ] Finally, and most intriguingly, the strain could be employed to enhance the optically detected magnetic resonance contrast.…”
Section: Figurementioning
confidence: 99%
“…[ 3c,26 ] We envision that two or more emitters in hBN can be put in resonance by employing the strain methods using cantilever geometries, as an example. [ 3b,27 ] The technique is fully amenable to the engineering of emitter—cavity coupling, whereby the SPE ZPL can be strain tuned into resonance with the cavity mode. [ 4,28 ] Finally, and most intriguingly, the strain could be employed to enhance the optically detected magnetic resonance contrast.…”
Section: Figurementioning
confidence: 99%
“…It has been shown that already excitons in plain mono-and bilayer TMDCs react to external strain tuning [169,170] and that even the exciton-phonon coupling can be controlled in this way. [171] First works are proceeding in this direction by demonstrating that also the transition energy of the artificial atoms can be tuned by applying static strain fields, either by bending a micromechanic device [172] or by using a piezoelectric substrate to stretch the entire system. [173] A coupling of TMDC artificial atoms and mechanic resonators entirely made from the monolayer have to the best of our knowledge not yet been achieved.…”
Section: Artificial Atoms In Layered Materialsmentioning
confidence: 99%
“…[9,44] We envision that two or more emitters in hBN can be put in resonance by employing the strain methods using cantilever geometries, as an example. [8,45] The technique is fully amenable to the engineering of emitter -cavity coupling, whereby the SPE ZPL can be strain tuned into resonance with the cavity mode. [10,46] Finally, and most intriguingly, the strain could be employed to enhance the optically detected magnetic resonance contrast.…”
Section: Figure 2 Large Red and Blue Strain-induced Shifts In A-b mentioning
confidence: 99%